Multiple C2 domains and transmembrane region proteins (MCTPs) tether membranes at plasmodesmata - Brault, Marie L.; Petit, Jules D.; Immel, Françoise; Nicolas, William J.; Glavier, Marie; Brocard, Lysiane; Gaston, Amèlia; Fouché, Mathieu; Hawkins, Timothy J.; Crowet, Jean Marc; Grison, Magali S.; Germain, Véronique; et al. (EMBO Reports, 2019)
In eukaryotes, membrane contact sites (MCS) allow direct communication between organelles. Plants have evolved a unique type of MCS, inside intercellular pores, the plasmodesmata, where endoplasmic reticulum (ER)–plasma membrane (PM) contacts coincide with regulation of cell-to-cell signalling. The molecular mechanism and function of membrane tethering within plasmodesmata remain unknown. Here, we show that the multiple C2 domains and transmembrane region protein (MCTP) family, key regulators of cell-to-cell signalling in plants, act as ER-PM tethers specifically at plasmodesmata. We report that MCTPs are plasmodesmata proteins that insert into the ER via their transmembrane region while their C2 domains dock to the PM through interaction with anionic phospholipids. A Atmctp3/Atmctp4 loss of function mutant induces plant developmental defects, impaired plasmodesmata function and composition, while MCTP4 expression in a yeast Δtether mutant partially restores ER-PM tethering. Our data suggest that MCTPs are unique membrane tethers controlling both ER-PM contacts and cell-to-cell signalling.
CRIS-Team Scopus Importer:2019-07-19
Keywords: ER-PM membrane contact sites; intercellular communication in plants; multiple C2 domains and transmembrane region proteins; plasmodesmata